Analisis Risiko Postur Tubuh Saat Memasang Roda Mobil Menggunakan Metode Rapid Entire Body Assessment (REBA) pada PT Plaza Auto Prima Tendean - Sunardi Sunardi; Nova Pangastuti; Sepriandi Parningotan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
In the current era of globalization, information technology is developing rapidly. As for technology, which is equipment created to make human work easier, when achieving good progress in the work process of PT Plaza Auto Prima, it is absolutely necessary to have a technique that supports and provides satisfactory service for customers. Based on this, the author tries to analyze a method used when employees work in the Plaza Auto Prima environment regarding the work ergonomics they currently apply at PT Plaza Auto Prima, which to date has not seen any improvement. The method used is direct observation and assessment of work posture using the REBA method. The research subjects were mechanics who worked in the installation or removal of car wheels. The data obtained is analyzed to determine the REBA score and the level of risk faced by workers. The research results show that the mechanical work posture at PT Plaza Auto Prima (Toyota) Tendean has significant problems. Analysis using the REBA method produces a final score of 8, which indicates a high risk level and requires immediate improvement. Factors that contribute to this high risk include the lack of ideal work ergonomics and limited supporting equipment. This increases the risk of injury and illness to the worker's body in the future. After improvements were made by adding trolley service tools, the way of working became more ergonomic so that the REBA score dropped to 2, which shows that some of the movements carried out were in the safe category or did not cause muscle injuries in the future. Therefore, the presence of bodily abnormalities that arise from work cannot be separated from the existence of supporting equipment to facilitate the removal of certain parts so as not to cause abnormal bodily effects. Planning for the procurement of a particular tool needs to be done as soon as possible so that workers do not suffer the effects of bodily abnormalities. In this way, the author took analytical steps using the Rapid Entire Body Assessment (REBA) method, which is the best solution to solve the problems that exist in this company to support workers so they can work all the time without any complaints about their bodies.